The Relationship between Nurse Workload and Attitudes in Fulfilling Spiritual Needs in Hospital Inpatient Rooms Bhakti Husada Cikarang - Farozi Farozi; Septiwiyarsi Septiwiyarsi; Rini Nurdini; Syarifudin Syarifudin (Lembaga Pengembangan Kinerja Dosen, 2024)
Nurses are professional health workers who, in carrying out their duties and responsibilities, are required to be able to fulfill their spiritual needs while working. This is because health services are a basic human need that is provided through health services not only in the form of physical aspects , but also psychological aspects. High spirituality will have an impact on intrapersonal, interpersonal and transpersonal relationships in overcoming various life problems. This research aims to determine the relationship between nurse workload and attitudes towards fulfilling spiritual needs in hospital inpatient rooms. Bhakti Husada Cikarang. The research design used cross sectional . The population is inpatient nurses who work in health services, namely at the Bhakti Husada Cikarang Hospital. The total population in this study was 84 nurses . The sampling technique used was accidental sampling , totaling 47 respondents. The statistical test used is the Chi Square test. The research results showed that the majority of respondents had a moderate workload, 27 people (57.4%) and 33 people (70.2%) had their spiritual needs met. The statistical test results obtained a p value of 0.89, meaning there is no relationship between nurses' workload and the fulfillment of spiritual needs. It is hoped that nurses will always improve their professionalism in carrying out nursing care.